Post-Saalian transformation of dry valleys in eastern Europe: An example from NE Poland. (20th February 2018) - Woronko, B.; Rychel, J.; Karasiewicz, T.M.; Kupryjanowicz, M.; Adamczyk, A.; Fiłoc, M.; Marks, L.; Krzywicki, T.; Pochocka-Szwarc, K.
Abstract: The studies were conducted in a dry valley in NE Poland. They were aimed at determining the origin of this structure and tracing the processes that have shaped the dry valley in a time span of about 130 ka. The research included detailed geological mapping, including piercing of a number of boreholes and electrical resistivity tomography (ERT) surveys. The obtained material was pollen analysed, OSL dated, and the grain size distribution and the morphoscopy of sand quartz grains were investigated; additionally the organic matter (OM) content was determined. Based on the obtained results it was concluded that the structure currently occupied by sediments of the dry valley was formed during the Warta Stadial of the Odranian Glaciation (Saalian; MIS 6) as a glacial tunnel valley. Small, probably isolated depressions functioned in the dry valley bottom after the ice sheet retreat. The sediments record a full succession of climate oscillations from the Eemian Interglacial (MIS 5e) (pollen zones E1 to E7) through the Early Vistulian (MIS 5a-5d) to MIS 4. In the Early Vistulian, the depressions functioned as lakes, or got shallower and were replaced by peat-bogs, depending on the climate conditions. During MIS 4, the bottom of the dry valley was subjected to erosion as a result of concentrated water flow. This caused draining of the existing depressions and their incorporation within the flow. Probably during MIS 3, solifluction was activated on the slopes of the dry valley. During LGM, permafrost aggradation occurred in the study area, recorded by two generations of epigenetic sand wedges and development of aeolian processes. In contrast to analogous processes within the European Sand Belt, the latter processes acted for a short time and only locally. The final record are Holocene soils. It seems that the analysed valley is a good example of palaeoenvironmental conditions in Eastern Europe.